Nursing professionals absenteism at a university hospital: a quantitative analysis - Fernanda da Cunha Ferroni; Zenith Rosa Silvino; Bárbara Pompeu Christovam (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The nursing human resources, according to the development of several strategies to answer the assistance requirement, viewing the several kinds of absenteeism among the nursing servers, have made us investigate quantitatively the absenteeism by illness / accident at the job place of the nursing professinals at a university hospital during 2007-2008. The general Objective: to establish the absenteeism enhances by illness / accident at job with the nursing professionals; specific objectives: to identify through Medical Expertise Survices at the hospital the absences from the service by the nursing professional getting an illness; to know from the noticed cases at the Accident Notification Service with biological material and to identify from the Inner Job Accident Communication (IJAC) the kinds of accidents causing absence from job. It is a non-experimental board investigation like survey, descriptive/exploratory. Intending with the investigation to offer fund/basis to the institution for a new human resources policy turned into the worker health, mobilizing the solicitors and other professionals for a continuous participative investigation pact about the job condition at all the unities, in order to foreview troubles and solutions together. Contributing for the Institution in the production of work absenteeism diagnostics, identified as one of the causes for the nursing professionals to get sick.